Proposed Model for Benchmarking in Quality of Arabian Universities: A Comparative Study between The Algerian University of Jijel and the University of Jordan - Belalta, Mebarak; Bouhali, Ratiba (The Arab Journal of Administration, 2018)
University education represents the most important pillars of the development of human societies, by the preparation of the workforce that they can possess high skills to qualify for entry to the local job market and competition in global level, in addition to the necessity of research progress and make targeted to solve the problems of society. The quality improvement became de center interesting of country, society and individuals. This study focused on display to the literature of quality in university and offers basic pillars to improve it by benchmarking method, through the model of gaps identifying which suggested and applicate on Jijel University, drawing on the achievements of Jordan University in the march towards improving quality and orientation towards the world. The most important finding that the study has attained are: there is a shortage in electronic libraries and distinctive university environment; and the Jordan University achieved 3 stars in Qs class, however Jijel University is still work to pass weaknesses, but without a define referential and approach. It also found positive gaps, no gaps and the other negative that need a plan for backfilling or reduced. Therefore Jijel University have to develop a vision defines ambition in the field of improving quality to be achieved in over a specific time frame and the adoption of a practical referential model.